Les enjeux de l’implantation de l’approche neurolinguistique, une nouvelle méthode d’apprentissage du français langue seconde auprès d’élèves allophones en contexte scolaire - Delphine Guedat-Bittighoffer; Marie-Ange Dat; Camille Humeau; Isabelle Nocus (Recherches en Éducation)
In France, allophone pupils face a difficult situation within the french school system with respect to the acquisition of french as a second language (FSL). How to have FSL acquired by these young migrant learners – both oral and writing skills – within a short timeframe, when some of them have not received previous schooling in their country of origin? The neurolinguistic approach (NLA) is a way to teach french as a second or foreign language, developed by Germain and Netten in 1997. It seemed pertinent to evaluate whether the NLA could facilitate the acquisition of language competencies while providing the pupils with an affectively safe environment. The main purpose of this article is to present the qualitative results of the first year of the project, which has been piloted since 2019 and during which the NLA has been applied in three introductory classes for allophone pupils.